Pathogenic mycoflora of clematis plants in Forest-Steppe of Ukraine - Shevchuk, O.; Afanasieva, O.; Makarenko, N.; Golosna, L.; Zlenko, D.; Kryvosheiev, S. (Quarantine and plant protection, 2024)
Goal. Identification of the fungi present in the plant tissues and rhizosphere of clematis and evaluation of their isolation frequency. Methods. Laboratory — plant samples collected in 2023—2024 throughout the growing season on three varieties were analyzed in the laboratory using macroscopic and biological methods. Isolation of fungi from the rhizosphere soil was carried out by the method of serial soil dilutions on agarized medium. The pathogens were identified by the cultural and morphological characteristics of the colonies and morphometric features of sporulation. Results. Nine species of fungi were isolated from the tissues of clematis leaves and stems, and eight species — from the root system and rhizosphere. The genus Alternaria was the most prevalent on leaves and stems, being observed throughout the entire growing season and isolated from 91% of the samples. Cladosporium spp. and Fusarium spp. were less common (isolation rate 58% and 17%, respectively). Neopestalotiopsis spp., Trichothecium spp., Cylindrocarpon spp., Epicoccum spp., and Chaetomium spp. were also found during both years of the study. Among the isolated fungi vast majority are pathogenic to plants. In 2024, symptoms of rust caused by Aecidium clematidis were detected. Rhizoctonia spp. and Fusarium spp. were most often isolated from the root system and rhizosphere soil. Conclusions. The results obtained indicate that throughout the growing season, plant pathogenic fungi were isolated from the leaves, stems, root systems, and rhizosphere soil. Alternaria spp. were predominantly found in the aboveground parts of the plants, while Rhizoctonia spp. and Fusarium spp. were primarily associated with the underground parts. These species, along with Neopestalotiopsis spp. and Cylindrocarpon spp., require constant monitoring, as they can cause damage on plants under favorable conditions for their development. Monitoring of mycoflora during the growing season makes it possible to establish the optimal periods for disease management.